2000
DOI: 10.1097/00005373-200007000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Selectin Blockade with a Small Molecule Inhibitor Downregulates Liver Chemokine Expression and Neutrophil Infiltration after Hemorrhagic Shock

Abstract: This study supports the role that selectins play in the pathogenesis of hemorrhagic shock. The mechanism of protection seen after multiple selectin blockade (TBC-1269) centered, in part, around the infiltration of liver neutrophils, probably dependent on the induction of macrophage inflammatory protein-2 and cytokine-induced neutrophil chemoattractant mRNA expression in liver tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Since AAG treatment significantly decreased the levels of AST and ALT, it suggests that this agent prevents/decreases the subsequent liver damage following trauma-hemorrhage and resuscitation. Based on previous studies [26], we postulate that the decreased leukocyte infiltration could be responsible for this protection. However, other potential protective mechanism such as the prevention of TNF-␣-induced apoptosis [27] or the modulation of platelet aggregation [3] could also play an important role in the observed beneficial effects.…”
Section: Discussionmentioning
confidence: 73%
“…Since AAG treatment significantly decreased the levels of AST and ALT, it suggests that this agent prevents/decreases the subsequent liver damage following trauma-hemorrhage and resuscitation. Based on previous studies [26], we postulate that the decreased leukocyte infiltration could be responsible for this protection. However, other potential protective mechanism such as the prevention of TNF-␣-induced apoptosis [27] or the modulation of platelet aggregation [3] could also play an important role in the observed beneficial effects.…”
Section: Discussionmentioning
confidence: 73%
“…Here, we report that E-selectin-mediated coclustering of L-selectin and PSGL-1 was dependent on lectin domain recognition of sLe x . Remarkably, pretreatment of E-selectin with the di-sLe x mimetic TBC1269, a small molecule currently being studied as an anti-inflammatory therapeutic, had a greater affect on the transition to arrest than did capture and rolling of neutrophils in the PPFC (26,42,43). Inhibition with TBC1269 increased the fraction of rolling neutrophils by ϳ25%, but decreased arrest by ϳ50%.…”
Section: Recognition Of Sle X On L-selectin and Psgl-1 By E-selectin mentioning
confidence: 99%
“…Our group has performed extensive work to determine the function, biochemistry, and molecular biology of the ischemic injury [52][53][54][55][56][57][58][59][60][61]. We have found that the Akt pathway plays an essential role in the phosphoregulation of acute inflammatory processes secondary to I/R injury.…”
Section: Phosphoregulation Of Inflammation Secondary To I/r: Our Currmentioning
confidence: 99%